2022
DOI: 10.1159/000522573
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Intermediate Nucleus of the Thalamus versus Posterior Subthalamic Area: Network Meta-Analysis of DBS Target Site Efficacy for Essential Tremor

Abstract: <b><i>Background:</i></b> Deep brain stimulation (DBS) targeting the ventral intermediate nucleus (Vim) of the thalamus or the posterior subthalamic area (PSA) are effective treatments for essential tremor (ET). However, their relative efficacy is unknown. <b><i>Objective:</i></b> Here, we present the first systematic review and network meta-analysis, examining the efficacy of Vim versus PSA DBS for treating medically refractory ET. <b><i>Methods:<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…In this retrospective, single‐center, single‐blinded pilot study of 9 patients, unilateral thalamotomy with MRIg‐LITT had an acceptable profile of AEs and led to improvement in tremor and QOL of patients with medically intractable ET. We successfully targeted and ablated the VIM nucleus of the thalamus, resulting in expected clinical outcomes that are comparable to those seen with RF, GKRS, and MRIg‐FUS thalamotomies 9,10,23 . In our study, we observed an 83.37% reduction in tremor at 12 months, compared to 74% to 90% for RF thalamotomy, 48% to 63% for GKRS thalamotomy, and 35% to 75% for MRIg‐FUS thalamotomy reported in a literature review 23 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In this retrospective, single‐center, single‐blinded pilot study of 9 patients, unilateral thalamotomy with MRIg‐LITT had an acceptable profile of AEs and led to improvement in tremor and QOL of patients with medically intractable ET. We successfully targeted and ablated the VIM nucleus of the thalamus, resulting in expected clinical outcomes that are comparable to those seen with RF, GKRS, and MRIg‐FUS thalamotomies 9,10,23 . In our study, we observed an 83.37% reduction in tremor at 12 months, compared to 74% to 90% for RF thalamotomy, 48% to 63% for GKRS thalamotomy, and 35% to 75% for MRIg‐FUS thalamotomy reported in a literature review 23 .…”
Section: Discussionsupporting
confidence: 70%
“…Deep brain stimulation (DBS) of the VIM nucleus is an effective therapy for medically intractable ET but may not be an option for many patients due to various sociomedical reasons or specific contraindications (patient preferences, cost implications, and follow‐up requirements; the necessity for ongoing magnetic resonance imaging [MRI] surveillance of existing cerebral pathologies; challenges faced by patients already equipped with cardiac pacemakers; and the unique demands of individuals engaged in certain professions or sports) 7,8 . Alternative lesional brain surgery procedures, such as thalamotomy using radiofrequency (RF), gamma‐knife radiosurgery (GKRS), or magnetic resonance imaging–guided focused ultrasound (MRIg‐FUS), have been shown to be efficacious to manage tremor symptoms in individuals for whom DBS is unsuitable 5,9,10 …”
mentioning
confidence: 99%
“…However, a randomized, double-blind, crossover trial by Barbe et al [18] identified that PSA DBS is equally effective and more efficient than VIM DBS after 1-year-use. A recent meta-analysis also demonstrated modest superior efficacy of PSA stimulation for treating refractory ET in the short-term follow-up [19]. In addition, simultaneous targeting of VIM and PSA via one trajectory is possible because simply advancing the electrode more deeply from VIM can reach the PSA accurately [20].…”
Section: B Amentioning
confidence: 99%
“…independently screened all titles and abstracts based on the following inclusion and exclusion criteria. 16 The inclusion criteria were (1) the study population comprised patients with only ET, (2) the patients received either unilateral SRS-T or FUS-T, and (3) tremor severity in the study was scored using a validated tremor scoring scale. Exclusion criteria were (1) all articles not available in English; (2) studies that involved animals, without any human participants; (3) technical analyses; (4) editorials; (5) literature or systematic reviews; (6) case reports or series with <5 patients; and (7) follow-up ≤3 months (Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%